2015
DOI: 10.13110/humanbiology.87.4.0361
|View full text |Cite
|
Sign up to set email alerts
|

Combating Racial Health Disparities through Medical Education: The Need for Anthropological and Genetic Perspectives in Medical Training

Abstract: Despite major public health initiatives, significant disparities persist between racially-and ethnically-defined groups in the prevalence of disease, access to medical care, quality of medical care, and health outcomes for common causes of morbidity and mortality in the United States. It is critical that we develop new and creative strategies to address such inequities, mitigate the social, environmental, institutional, and genetic determinants of poor health, and combat the persistence of racial profiling in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…While some medical schools have courses on racial disparities in health, critical race theory to help contextualize racial health disparities is not a requirement. In fact, in most medical school curricula, race is framed as biological or as a biological risk factor, implying that racial disparities in health are innate and can be explained without implicating racism . This fosters pathologizing race rather than racism, whereas racism is the risk factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some medical schools have courses on racial disparities in health, critical race theory to help contextualize racial health disparities is not a requirement. In fact, in most medical school curricula, race is framed as biological or as a biological risk factor, implying that racial disparities in health are innate and can be explained without implicating racism . This fosters pathologizing race rather than racism, whereas racism is the risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in most medical school curricula, race is framed as biological or as a biological risk factor, implying that racial disparities in health are innate and can be explained without implicating racism. [30][31][32][33] This fosters pathologizing race rather than racism, whereas racism is the risk factor. Naming racism in medical education, health services research and policy, and how it is distinct from race as a category can advance efforts to reduce racial health inequities.…”
Section: Center the Marginsmentioning
confidence: 99%
“…Other scholars have documented this racial folklore and found that physicians believe race is biological and that the “human genomic variation maps neatly onto American racial categories” (Baer et al., 2013; Bolnick, 2015; Braun et al., 2007; Hunt et al., 2013; Tuckson et al., 2013). These doctors have either not been exposed to, or have a schema which enables them to ignore “a sizable body of scientific literature shows that most health disparities are caused by social and environmental factors” (Bolnick, 2015).…”
Section: Can Doulas Do Their Work Within the Hospital System?mentioning
confidence: 99%
“…These adaptations can cause visible phenotypic changes to skin colour, but this has no relation to an individual's essential nature as race thinking would suggest: “the genes underlying phenotypic differences used to assign race categories are atypical of the genome in general and are not a reliable index to the amount of genetic differentiation between groups” (Feldman & Lewontin, , p. 97). This fact may account for the increasing evidence that racial profiling for medical purposes in the United States, using culturally derived categories such as “Black” and “White,” is harming some patients instead of helping them (Bolenick, ).…”
Section: Introductionmentioning
confidence: 99%
“…"the genes underlying phenotypic differences used to assign race categories are atypical of the genome in general and are not a reliable index to the amount of genetic differentiation between groups" (Feldman & Lewontin, 2008, p. 97). This fact may account for the increasing evidence that racial profiling for medical purposes in the United States, using culturally derived categories such as "Black" and "White," is harming some patients instead of helping them (Bolenick, 2015). This is not to say that racial categories are wholly without value.…”
mentioning
confidence: 99%